2015
DOI: 10.1038/pj.2015.38
|View full text |Cite
|
Sign up to set email alerts
|

Tripodal polyhedral oligomeric silsesquioxanes as a novel class of three-dimensional emulsifiers

Abstract: Tripodal amphiphilic molecules toward organic-inorganic hybrid emulsions were successfully synthesized based on incompletely condensed polyhedral oligomeric silsesquioxanes (POSSs). The three silanol groups provide an excellent scaffold for the construction of three-dimensional amphiphilic molecules, thus well-defined tripodal amphiphilic POSS derivatives were readily synthesized. Thermal analyses revealed that an incompletely condensed POSS exhibited lower crystallinity without loss of thermal stability in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…At the same time, chemists are looking for synthetic routes exploiting among others hydrosilylation reaction to obtain novel, functionalized Si-based reagents with a specific structure such as silsesquioxanes. [17][18][19][20][21][22][23][24][25][26][27] While hydrosilylation of olefins with silanes has been widely studied, [3,28] the reports on T 8 silsesquioxanes are limited [5,6,[29][30][31][32][33][34] and for double-decker systems of both closed (D 2 T 8 [4,19,25,[35][36][37] ) and opened (M 4 T 8 [38][39][40][41][42][43] ) structure even more scant. [5] Cage-like derivatives have driven much attention due to specific physicochemical properties (governed by the nature of their silicate rigid core and by the number and type of functional groups attached to it) affecting directions of their broad applications from material chemistry to medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, chemists are looking for synthetic routes exploiting among others hydrosilylation reaction to obtain novel, functionalized Si-based reagents with a specific structure such as silsesquioxanes. [17][18][19][20][21][22][23][24][25][26][27] While hydrosilylation of olefins with silanes has been widely studied, [3,28] the reports on T 8 silsesquioxanes are limited [5,6,[29][30][31][32][33][34] and for double-decker systems of both closed (D 2 T 8 [4,19,25,[35][36][37] ) and opened (M 4 T 8 [38][39][40][41][42][43] ) structure even more scant. [5] Cage-like derivatives have driven much attention due to specific physicochemical properties (governed by the nature of their silicate rigid core and by the number and type of functional groups attached to it) affecting directions of their broad applications from material chemistry to medicine.…”
Section: Introductionmentioning
confidence: 99%
“…[12,15,16] Taking research in the field of macromolecular DDSQ-based frameworks of hybrid nature into account, difunctionalized doubledecker silsesquioxanes are of greatest interest due to the possibility of their incorporation into the main chain of the polymer. [17][18][19][20][21][22][23][24][25][26][27] While hydrosilylation of olefins with silanes has been widely studied, [3,28] the reports on T 8 silsesquioxanes are limited [5,6,[29][30][31][32][33][34] and for double-decker systems of both closed (D 2 T 8 [4,19,25,[35][36][37] ) and opened (M 4 T 8 [38][39][40][41][42][43] ) structure even more scant. Miyashita and co-workers were the first to apply hydrosilylation as a method to modify tetrahydrosubstituted DDSQ (DDSQ-4OSiH) compound with N-vinylcarbazole performed in the presence of Karstedt's catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dumbbell- 21,22 and star-shaped 23,24 POSS oligomers (dimer and nonamer, respectively) produce optically transparent amorphous films, whereas monomeric POSS compounds form turbid aggregates. 27 Notably, melting point of IC-POSS is remarkably lowered from CC-POSS, while there is no significant difference in thermal stability. 27,28 An emulsifier based on IC-POSS stabilizes the emulsions, but that of CC-POSS analogue did not work.…”
Section: Introductionmentioning
confidence: 96%
“…It has been found that collapse of the symmetry of POSSs is an effective technique for suppression of the crystallinity. 27,28 An emulsifier based on IC-POSS stabilizes the emulsions, but that of CC-POSS analogue did not work. Recently, we have found that incompletely-condensed POSSs [IC-POSSs, Chart 1(b)], which are traditionally employed as precursors for monofunctionalized completely condensed POSSs [CC-POSSs, Chart 1(a)], 25,26 possess excellent dispersibility due to the lowsymmetrical and flexible open-cage structure.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, open-cage silsesquioxanes, i.e., not-completely condensed systems have recently attracted much attention. The silsesquioxane trisilanol precursors enable the introduction of three reactive substituents to the Si-O-Si core by means of stoichiometric (hydrolytic condensation), but also catalytic (e.g., hydrosilylation, arylation, O-silylation), processes using functional groups that are already attached to the SQ core [8][9][10][11][12][13][14][15][16]. The symmetry of their trifunctional T 7 open-cage derivatives is changed due to the lack of one vertex in the structure, which affects their physical properties (i.e., changes in molecular packing, melting points) [9,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%